Sensitivity and Selectivity on Aptamer-Based Assay: The Determination of Tetracycline Residue in Bovine Milk - Sohee Jeong; Insook Rhee Paeng (The Scientific World Journal)
A competitive enzyme-linked aptamer assay (ELAA) to detect tetracycline in milk was performed by using two different aptamers individually; one is 76 mer-DNA aptamer and the other is 57 mer-RNA aptamer. The best optimum condition was obtained without monovalent ion, Na+ and also by adding no Mg2+ ion in the assay buffer, along with RT incubation. The optimized ELAA showed a good sensitivity (LOD of 2.10 × 10−8 M) with a wide dynamic range (3.16 × 10−8 M ~ 3.16 × 10−4 M). In addition, the average R.S.D. across all data points of the curve was less than 2.5% with good recoveries (~101.8%) from the milk media. Thus, this method provides a good tool to monitor tetracycline in milk from MRLs’ point of view. However, this ELAA method was not superior to the ELISA method in terms of specificity. This paper describes that it does not always give better sensitivity and specificity in assays even though aptamers have several advantages over antibodies and have been known to be good binders for binding assays.